Effects of sulfur application on sulfur and arsenic absorption by rapeseed in arsenic-contaminated soil - L. Zhong; C. Hu; Q. Tan; J. Liu; X. Sun (Plant, Soil and Environment, 2011)
A pot experiment was conducted to study the effects of arsenic (As) and sulfur (S) interaction on yield and their accumulation and distribution in rapeseed (Brassica napus L.). The results showed that (1) at the same level of S treatment, application of As significantly decreased rapeseed grain and biomass yield; (2) Application of S significantly increased the grain and biomass yield of rapeseed when As was applied; (3) When As application rate increased, As content significantly increased in different parts of rapeseed, and reached their highest level at120 mg/kg As. Arsenic content from seed were all below 1 mg/kg AS. Addition of S significantly reduced As contents in root and grain of rapeseed.